2014
DOI: 10.4236/ajps.2014.526421
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alkaloid’s Profile in Ficus benjamina L. Extracts with Higher Antioxidant Power

Abstract: Different classes of known alkaloid compounds were identified for the first time in leaves and barks of Ficus benjamina L. from Moraceae family. The identification of 28 alkaloids in F. benjamina leaves and 14 alkaloids in its barks was identified using chromatographic analysis as Gas Chromatography associated to Mass Spectrometry (GC-MS). This characterization analysis allows to verifying the presence of different alkaloids type-classes in both leaves and barks, such as isoquinoline class, indole class and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Alkaloids are one of the secondary metabolites found in plants, which can be found in leaves, branches, seed, and bark, (Aksara, Musa, & Alio, 2013). Novelli, Lorena, & Antonella (2014) reported that alkaloid contained in Ficus benjamina L. crude extract, had a strong correlation with its antioxidant.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids are one of the secondary metabolites found in plants, which can be found in leaves, branches, seed, and bark, (Aksara, Musa, & Alio, 2013). Novelli, Lorena, & Antonella (2014) reported that alkaloid contained in Ficus benjamina L. crude extract, had a strong correlation with its antioxidant.…”
Section: Resultsmentioning
confidence: 99%
“…For example, P. aquatica accumulates high contents of the fungitoxin isohemigossypolone in the outer bark of the below-ground part of the swollen trunk (Shibatani et al , 1999) and it has been found to be a weak isoprene emitter (Taylor et al , 2018). Ficus species contain numerous secondary plant metabolites such as alkaloids (Baumgartner et al , 1990; Khan et al , 1993; Novelli et al , 2014) and in contrast to P. aquatica they have been found to be strong isoprene emitters (Wyche et al , 2014). Many bioactive constituents such as cinnamic acids, lactose, naringenin, quercetin, caffeic acid, and stigmasterol as well as 28 different alkaloids have been identified in F. benjamina (Novelli et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the purified alkaloids from Amaranthus viridis leaves have protective effects in vitro conditons against hydrogen peroxide induced oxidative damage in human erythrocytes through decreasing Lipid peroxidation levels [55]. On the same side, Novelli et al [56] identified of 28 alkaloids in leaves of Ficus benjamina and 14 alkaloids in its barks. A significant correlation was observed between the total alkaloid content of crude extracts and 2,2-diphenyl-1-picrylhydrazyl assay (DPPH), suggesting that the level of antioxidant activity in this species is strongly correlated to the alkaloid content.…”
Section: Alkaloidsmentioning
confidence: 99%